Validation of a predictive model coupling gas transfer and microbial growth in fresh food packed under modified atmosphere. (September 2016) - Guillard, V.; Couvert, O.; Stahl, V.; Hanin, A.; Denis, C.; Huchet, V.; Chaix, E.; Loriot, C.; Vincelot, T.; Thuault, D.
Abstract: Predicting microbial safety of fresh products in modified atmosphere packaging implies to take into account the dynamic of O2, CO2 and N2 exchanges in the system and its effect on microbial growth. In this paper a mechanistic model coupling gas transfer and predictive microbiology was validated using dedicated challenge-tests performed on poultry meat, fresh salmon and processed cheese, inoculated with either Listeria monocytogenes or Pseudomonas fluorescens and packed in commercially used packaging materials (tray + lid films). The model succeeded in predicting the relative variation of O2, CO2 and N2 partial pressure in headspace and the growth of the studied microorganisms without any parameter identification. This work highlighted that the respiration of the targeted microorganism itself and/or that of the naturally present microflora could not be neglected in most of the cases, and could, in the particular case of aerobic microbes contribute to limit the growth by removing all residual O2 in the package. This work also confirmed the low sensitivity of L. monocytogenes toward CO2 while that of P. fluorescens permitted to efficiently prevent its growth by choosing the right combination of packaging gas permeability value and initial % of CO2 initially flushed in the pack. Highlights: Bacterial respiration could not be neglected to predict gas transfer and microbial growth. Listeria monocytogenes growth is not inhibited by CO2 at atmosphere pressure. Pseudomonas fluorescens is adequately controlled by high level of CO2 (>40%). Rapid consumption of residual O2 after packing impacts greatly aerobic species growth. The mathematical model helps to design efficient Modified Atmosphere System.